2011
DOI: 10.1089/ars.2010.3504
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Liaisons of p53

Abstract: Mitochondria play a central role in cell survival and cell death. While producing the bulk of intracellular ATP, mitochondrial respiration represents the most prominent source of harmful reactive oxygen species. Mitochondria participate in many anabolic pathways, including cholesterol and nucleotide biosynthesis, yet also control multiple biochemical cascades that contribute to the programmed demise of cells. The tumor suppressor protein p53 is best known for its ability to orchestrate a transcriptional respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
63
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 259 publications
(270 reference statements)
1
63
0
Order By: Relevance
“…Activated TP53 exerts lethal functions via nuclear and cytoplasmic mechanisms that eventually lead to mitochondrial outer membrane permeabilization or increased signaling via death receptors followed by cell death (Kroemer et al, 2007;Galluzzi et al, 2011) In response to cisplatin, CHEK1 has also been shown to activate various branches of the mitogenactivated protein kinase (MAPK) system, including those mediated by extracellular signal-regulated kinases, c-JUN N-terminal kinases and stress-activated protein kinases (Persons et al, 2000;Wang et al, 2000;Dent and Grant, 2001;Yeh et al, 2002). The relative contribution of these signaling modules to the cytotoxic effects of cisplatin remain to be deciphered, as contrasting reports can be found in literature (Dent and Grant, 2001).…”
Section: Mode Of Actionmentioning
confidence: 99%
“…Activated TP53 exerts lethal functions via nuclear and cytoplasmic mechanisms that eventually lead to mitochondrial outer membrane permeabilization or increased signaling via death receptors followed by cell death (Kroemer et al, 2007;Galluzzi et al, 2011) In response to cisplatin, CHEK1 has also been shown to activate various branches of the mitogenactivated protein kinase (MAPK) system, including those mediated by extracellular signal-regulated kinases, c-JUN N-terminal kinases and stress-activated protein kinases (Persons et al, 2000;Wang et al, 2000;Dent and Grant, 2001;Yeh et al, 2002). The relative contribution of these signaling modules to the cytotoxic effects of cisplatin remain to be deciphered, as contrasting reports can be found in literature (Dent and Grant, 2001).…”
Section: Mode Of Actionmentioning
confidence: 99%
“…In particular, p53 influences mitochondrial functions such as apoptosis and respiration which is the most prominent source of ROS. p53 was shown to indirectly promote mitochondrial functions and inhibit glycolysis [21][22][23]. The consequence of this promotion of oxidative phosphorylation is a decrease in oxidative stress and thus prevention of DNA damage.…”
Section: Redox Modificationsmentioning
confidence: 99%
“…However, in recent years the role of p53 in cytoplasm especially during autophagy, energy metabolism and mitochondrial functions (reviewed by Galluzzi et al, 2011;Green and Kroemer, 2009) have also come into sharper focus.…”
mentioning
confidence: 99%